Caracterização de uma monooxigenase lítica de polissacarídeo recombinante de Chromobacterium violaceum que apresenta atividade inibitória contra espécies de Candida - Queiroz, Bruno Roberto da Silva (2022)
LPMOs (lytic polysaccharide monooxygenases) constitute a class of enzymes, called auxiliary enzymes, which are characterized by their mechanism of oxidative cleavage of polysaccharides, enhancing the activities of canonical glycoside hydrolases, involved in the degradation of recalcitrant polysaccharides found in nature. Some LPMOs were identified in the genome of Chromobacterium violaceum ATCC 12472, including the LPMO encoded by the ORF CV2592. An initial analysis revealed that this LPMO has a modular structure, containing the LPMO_10 (peroxidase activity), GbpA_2 (N- acetylglucosamine binding domain) and ChiA1_DB (chitin binding domain) domains. Thus, the aim of this work was to analyze the functionality of this LPMO in relation to peroxidase-like activity and its inhibition potential on Candida species. In silico analysis revealed that CV2592 belongs to the AA10 family of auxiliary activity enzymes. All LPMOs have two conserved histidine residues in their catalytic site, forming a histidine arm whose function is to coordinate Cu2+ , which is essential for the oxidative activity of LPMOs. Recombinant LPMO (rCvLPMO-SUMO) fused to the solubility tag SUMO was expressed in Escherichia coli BL21(DE3) and purified by immobilized metal affinity chromatography, exhibiting an apparent molecular mass of 56 kDa. The identity of this protein was further confirmed by mass spectrometry, which produced peptides covering 45.3% of their primary structure. The in vitro characterization showed that rCvLPMO- SUMO has peroxidase activity on the substrate 2,6-dimethoxyphenol, demonstrating the functionality of the LPMO_10 catalytic domain. The functionality of the chitin binding domain, ChiA1_DB, was also confirmed by chitin matrix affinity chromatography. The optimal conditions for enzymatic activity were determined at pH 7.0 and temperature of 50 oC. rCvLPMO-SUMO was stable in relation to pH variation, maintaining at least 80% of its activity after being subjected to extreme pH values and a temperature of 60 °C. The rCvLPMO-SUMO activity is completely inhibited in the presence of 5 mM Fe3+, Ag+ and Hg2+ ions and 2% SDS, 5 mM EDTA and 100 mM DTT. Circular dichroism experiments indicate a Tm of 74.9 °C. rCvLPMO-SUMO presented inhibitory and lethal activities against several strains of Candida albicans, Candida parapsilosis and Candida tropicalis. Transmission electron microscopy (TEM) analysis evidenced the damage caused by rCvLPMO-SUMO to Candida cells. Cell viability analyzes and ROS production with propidium iodide and DCFH-DA, respectively, revealed that the protein causes permeabilization of the plasma membrane and induces the production of reactive oxygen species by Candida cells treated with rCvLPMO-SUMO.